Israel-Palestine - Strong, Nicholas, active 2018, (SAGE Business Cases., 2018)
Since Jewish immigrants began arriving in substantial numbers to what was then Ottoman Palestine during the late 19th century, a conflict between Israeli and Palestinian residents has raged. However, business leaders have stayed on the sidelines. For the most part, the conventional wisdom among private sector leaders was that a political settlement of the conflict would have to precede economic co-operation. Even if they had wanted to co-operate, the Israeli and Palestinian business communities were unconnected. Yet in 2013, prominent Israeli and Palestinian business people came together to challenge the conventional wisdom. Under the auspices of the World Economic Forum, they announced the first prominent joint Israeli-Palestinian private sector group agitating for peace building initiatives, Breaking the Impasse (BTI). The goal of the group was to lobby political authorities to work toward a two-state solution. After an initial flurry of activities, however, the group foundered and the Palestinian representatives withdrew.